Okay, let's talk - short debriefings in the operating room. Issue 7 (July 2020) - Mundt, Anna Sofie; Gjeraa, Kirsten; Spanager, Lene; Petersen, Susanne Skovsø; Dieckmann, Peter; Østergaard, Doris
Abstract: Introduction: Debriefing is increasingly used to enhance learning and reflection in clinical practice. Nevertheless, barriers to implementing debriefings in the operating room (OR) include lack of time, the availability of trained facilitators, and difficulty gathering the full team after surgery. Spending five minutes on a debriefing during skin closure or between procedures may enhance learning and reflection on practice, generating to improve patient safety. The aim of this study was to explore characteristics, feasibility and content of short debriefings in the OR. Methods: This was a mixed-method study of short debriefings, analyzing audio-recordings, field notes and relevance ratings from multi-professional teams, that conducted short debriefings in the OR at two University Hospitals in Denmark. Results: A total of 135 debriefings were conducted, with a median duration of five minutes (range 1:19 min–12:05 min). A total of 477 team members participated in the debriefings. The teams' median rating of relevance was 6 (range 1–10). The rating was higher following challenging events and in debriefings where the surgeon actively participated in the conversation. The teams discussed non-technical skills in all the debriefings and verbalized reflections on practice in 75 percent of the debriefings. Conclusion: It was feasible to conduct short debriefings in a production-focused, complex work environment. In all the debriefings, the teams discussed various non-technical skills (NTS) and reflected on practice. The majority of team members rated the debriefings as relevant for their task management. Abstract : Surgery; Abdominal Surgery; Orthopedics; Educational Development; Health Profession; Medical Education; Pedagogy; Cognitive Psychology; Debriefing; Operating room; learning; Teamwork; Non-technical skills